Avoidance of Hen's Egg Based on IgE Levels Should Be Avoided for Children With Hen's Egg Allergy - Yoshitsune Miyagi; Yoshitsune Miyagi; Kiwako Yamamoto-Hanada; Hiroya Ogita; Tomoyuki Kiguchi; Yusuke Inuzuka; Kenji Toyokuni; Koji Nishimura; Makoto Irahara; Fumi Ishikawa; Miori Sato; Mayako Saito-Abe; et al. (Frontiers Media S.A., 2021)
Background: Although hen's egg (HE) allergy was thought to be usually resolved by late childhood, majority of HE allergy patients with a high level of egg white (HEW)-specific IgE could not acquire tolerance for HE by age 8 years.Objective: The aim is to investigate whether the avoidance of HE until 6 years of age increased the risk of heated HE allergy at age 6 years.Methods: This was a retrospective case-control study. The HE tolerance children (n = 17) and children with low-dose HE reactor [a positive reaction to ≤ 4 g of heated HEW in oral food challenges (OFCs)] children (n = 26) were included based on the results of OFC at 6 years old. Multivariate logistic regression analysis was applied to examine the associations between HE avoidance until age 6 years and HE allergy status confirmed by OFC, adjusting the level of ovomucoid-specific IgE (OM-sIgE) during early infancy.Results: A lower proportion of strict avoidance of HE was observed in the HE tolerance group than in the low-dose HE reactor group (6 vs. 46%, p = 0.006). OM-sIgE levels in children younger than 2 years old were significantly higher in the low-dose HE reactor group than those in the HE tolerance group (median [interquartile], 26.7 UA/mL [11.9-53.4] vs. 7.9 UA/mL [0.35-23.4]; p =0.024). The avoidance of HE until 6 years of age increased the risk of heated HE allergy even after adjusting OM-sIgE levels.Conclusions: The long-term avoidance of HE from infancy increased the risk of heated HE allergy confirmed by OFC at age 6 years.